Pharmacokinetics-based chronoefficacy of Fuzi against chronic kidney disease. (25th January 2021) - Yang, Zemin; Lin, Yanke; Su, Chong; Wang, Shuai; Gao, Lu; Lin, Jingpan; Wang, Zhigang; Wu, Baojian
Abstract: Objectives: Identifying drugs with time-varying efficacy or toxicity, and understanding the underlying mechanisms would help to improve treatment efficacy and reduce adverse effects. In this study, we uncovered that the therapeutic effect of Fuzi (the lateral root of Aconitum carmichaelii Debeaux) depended on the dosing time in mice with adenine-induced chronic kidney disease (CKD). Methods: The Fuzi efficacy was determined by biomarker measurements [i.e. plasma creatinine (CRE), blood urea nitrogen (BUN) and urinary N-acetyl-β-D-glucosaminidase (NAG)], as well as inflammation, fibrosis and histological analyses. Circadian regulation of Fuzi pharmacokinetics and efficacy was evaluated using brain and muscle Arnt-like protein-1 (Bmal1)-deficient ( Bmal1 −/− ) mice. Key findings: The Fuzi efficacy was higher when the drug was dosed at ZT10 and was lower when the drug was dosed at other times (ZT2, ZT6, ZT14, ZT18 and ZT22) according to measurements of plasma CRE, BUN and urinary NAG. Consistently, ZT10 (5 PM) dosing showed a stronger protective effect on the kidney (i.e. less extensive tubular injury) as compared to ZT22 (5 AM) dosing. This was supported by lower levels of inflammatory and fibrotic factors ( IL-1β, IL-6, Tnf-α, Ccl2, Tgfb1 and Col1a1 ) at ZT10 than at ZT22. Pharmacokinetic analyses showed that the area under the curve (AUC) values (reflective of systemic exposure) and renal distribution of aconitine, hypaconitine and mesaconitine (three putative active constituents) for Fuzi dosing at ZT10 were significantly higher than those for herb dosing at ZT22, suggesting a role of circadian pharmacokinetics in Fuzi chronoefficacy. Drug efficacy studies confirmed that aconitine, hypaconitine and mesaconitine possessed a kidney-protecting effect. In addition, genetic knockout of Bmal1 in mice abolished the time-dependency of Fuzi pharmacokinetics and efficacy. This reinforced the existence of chronoefficacy for Fuzi and supported the role of circadian pharmacokinetics in Fuzi chronoefficacy. Conclusions: The efficacy of Fuzi against CKD depends on the dosing time in mice, which is associated with circadian pharmacokinetics of the three main active constituents (i.e. aconitine, hypaconitine and mesaconitine). These findings highlight the relevance of dosing time in the therapeutic outcomes of herbal medicines.